The clairvoyants : a novel - Brown, Karen, 1960- (New York : Henry Holt and Co., 2017)
"Karen Brown's most hypnotic novel to date--gothic-inflected psychological suspense that unmasks the secret desires of a young woman with a mystical gift. On the family homestead by the sea where she grew up, Martha Mary saw ghosts. As a young woman, she hopes to distance herself from those spirits by escaping to an inland college town. There, she is absorbed by a budding romance, relieved by separation from an unstable sister, and disinterested in the flyers seeking information about a young woman who's disappeared--until one Indian summer afternoon when the missing woman appears beneath Martha's apartment window, wearing a down coat, her hair coated with ice. "--
Keywords: Sisters -- Fiction; FICTION / Romance / Gothic; FICTION / Psychological; FICTION / Literary; Suspense fiction; Pyschological fiction; Ghost stories; Ghost stories; Paranormal fiction